(untitled) (Global Journal of Human-Social Science, 2012)
It has been widely argued that democracy is an imperative for development in the 21st Century Nigeria Perhaps it is because the concept has been tested in some societies particularly in western societies and it worked The paper argues that one of the reasons democratic institution has not yet been properly rooted in Nigeria is that it has been choked off and smothered by plutocracy The attendant consequences include impoverishment of the citizenry gradual deterioration of established democratic institutions and agencies and high level of criminality militancy and terrorist-oriented activities